Creation of a Provider Billing Website at PT Bank Tabungan Negara Jakarta (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Currently, PT Bank Tabungan Negara manages internet bills using SharePoint and Excel. This means that if there are errors or delays in billing or payment, PT Bank Tabungan Negara must provide information to the ISP provider. Based on this problem, there is a need to create a “Provider billing website at PT Bank Tabungan Negara Jakarta.” The purpose of this research is to develop a web-based Internet Bill Payment Information System at PT Bank Tabungan Negara. The system development methodology uses the SDLC (Software Development Life Cycle) method, and the system development uses a framework as well as PHP programming and a MySQL database. The total billing information at PT Bank Tabungan Negara consists of internet subscription fees and customer information that must be paid for internet subscriptions. Additionally, from the public's perspective, several forms and reports are generated, including a dashboard, client form, internet package form, fake network form, billing form, and summary form. The entire system has been implemented on a web-based platform. This system facilitates internet distribution management for staff and enables employees to access information regarding internet subscription payments.